Automated face localization and facial features detection using geometric information - Chai, Tong Yuen; Mohd Rizon, Mohamed Juhari, Prof. Dr.; Karthigayan, M.; Sugisaka, M.; Hazry, Desa, Dr.; Ibrahim, Z. (Malaysia-Japan University Center (MJUC), 2011)
Organized by Malaysia-Japan University Center (MJUC), 12th - 15th November 2007 at Seri Pacific Hotel, Kuala Lumpur, Malaysia.